HUMAN AND NATURE: SYSTEM, CO-EVOLUTION, CAPACITY - Ягодзінський, С. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The synergistic approach as a base in the study of the social and cultural potential of co-evolution of complex systems is analyzed.